Strategic management in healthcare: the impact of strategic decisions on achieving organizational goals and improving the quality of healthcare services - Andrieiev, Ie.; Trehub, D.; Khatsko, K.; Sokolovska, I. S.; Ganzhiy, I. Yu.; Соколовська, Ірина Сергіївна; Ганжий, Ірина Юріївна (My University, 2024)
Strategic management in healthcare and the process of making strategic decisions to achieve organizational goals and enhance healthcare quality represent a significant challenge in nations with established social protection systems. Prioritizing the development of human capital, reinforcing social protection mechanisms, and elevating the standard of living for the populace emerge as primary imperatives for governments seeking to establish an effective social protection system. Strategic decisions are formulated based on the comprehensive analysis of available analytical and statistical data regarding healthcare quality, culminating in the establishment of a strategic development trajectory for the healthcare sector. The principal objective of this study is to conduct an in-depth analysis of the central issues within the healthcare domain and identify efficacious strategic solutions that could contribute to the advancement and enhancement of healthcare services. The article critically examines the nuances of strategic management within the healthcare sector, and it offers a detailed segmentation of the sector along with proposals for potential enhancements tailored to each specific segment. Moreover, this study directs attention toward the healthcare systems within some of the world's most advanced nations, offering valuable insights that can inform the assimilation of foreign experiences for future adaptation. The article systematically examines the intricacies of strategic action planning and management within the healthcare sector, encompassing both the public and corporate sectors, as well as the engagement of transnational corporations. The primary objectives of this research encompass conducting a comprehensive investigation of the factors influencing the strategic evolution of healthcare and identifying potential measures for its enhancement. The findings presented in this article underscore the imperative of continual development and improvement in the quality of healthcare services. They emphasize the importance of making judicious strategic decisions to sustain the healthcare market's functionality and ensure its continued vitality.
Keywords: strategic management; strategic decisions; healthcare; medical services; pharmaceutical market; pharmaceuticals